Funny & Funnier - Shirshendu Mukhopadhyay (U.S.A Scholastic Inc, 2010)
This hilarious collection of ten stories has a host of amusing characters, like the cow and tiger that drank from the same pond, the thief who does not like to steal, and the king who issues random commands.
Keywords: Anthology Fiction -- Anthology Fiction